Isu-Isu Kontemporer Pendidikan Indonesia: Kesenjangan Pendidikan - Wijayanti, Anti; Darmawan, Ari Wawan; Marwan, Iis (Cendekia: Jurnal Pendidikan dan Pemberdayaan Masyarakat, 2024)
Abstract. The education gap is one of the significant contemporary issues in Indonesia, characterized by inequalities in access, quality and means of learning between regions, especially between urban and rural areas. Factors such as geographical conditions, economics, government policies and the quality of teaching staff are the main causes of this gap. The research method used in this study is a literature study, which aims to analyze data from various sources, including relevant research reports, books and journal articles. The results show that schools in urban areas are generally more advanced in terms of infrastructure and teacher quality compared to schools in rural areas, where education facilities and access are still very limited. In addition, the low availability of technology and resources in remote areas further exacerbates this disparity. To address these issues, more inclusive policies are needed, such as a more equitable distribution of the education budget, improving the quality of teacher training and utilizing technology for distance education. This study is expected to provide a more in-depth picture of the factors that exacerbate the education gap in Indonesia and provide recommendations to reduce the gap.